Up-converter nanophosphor Y2O2S:Er,Yb aminofunctionalized containing or not spherical silica conjugated with BSA - Gelamos, Joao Paulo [UNESP]; Laranja, Marlon Larry [UNESP]; Lombardi Alvino, Karla Cristina [UNESP]; Camacho, Sabrina Alessio [UNESP]; Pires, Ana Maria [UNESP] (Elsevier B.V., 2009)
This work reports on the study of the nanophosphor. Y2O2S:Er(2%),Yb(1%) obtained from polymeric resin to be evaluated as fluorescent label with Suitable features to conjugate with bio-molecules for bioassay up-converting phosphor technology (UPT) application A conjugation protocol between bovine serum albumin (BSA) and the aminofunctionalized nanophosphor containing or not spherical silica was established UV-vis results indicated an effective conjugation between nanophosphor particles and the protein up-conversion measurements under 980 nm excitation performed for samples before and after aminofunctionalization showed that nanophosphor particles luminescence features keep unchanged in all cases All results suggest that the adapted protocol is feasible to provide a nanoparticle-protein effective conjugation preserving nanophosphor optical features The presence of spherical silica can be considered advantageous to increase conjugation efficiency Therefore. the developed procedure is applicable for future conjugations between the chosen nanophosphor and the streptavidin protein chat takes part in the well known self-recognition system avidin-biotin. (C) 2009 Elsevier B.V All rights reserved.
Keywords: Functionalised spherical silica; Up-converter; Nanophosphor; Label agent; Biological assay